A Method for Determining Feasibility of Mining Residual Coal above Out-Fashioned Goaf under Variable Load: A Case Study. (27th August 2020) - Guo, Yuxia; Yuan, Honghui; Deng, Xiaogang; Zhang, Yujiang; Du, Yunlou; Liu, Hui; Feng, Guorui; Xu, Jiali; Zhao, Renle; Doan, Dao Viet
Abstract : Out-fashioned goaf is the protective structure for mining the upper residual coal, and its stability is the core problem in mining the upper residual coal. According to the upward mining demand for No. 5 coal seam above the out-fashioned goaf in Baizi Coal Mine, a new method is proposed to determine the upward mining safety. According to the analysis of the actual situation of the mine, the coal pillar and suspended roof in the out-fashioned goaf are taken as the objects. Furthermore, a "coal pillar-suspended roof" system model based on the variable load induced by abutment pressure of upper coal seam mining is established. After the mechanical model was solved, the parameter acquisition method of the model was established. The basic parameters of Baizi Coal Mine were considered to determine the feasibility of mining residual coal above out-fashioned goaf. And the effects of variable load on the coal pillar and suspended roof stability were analyzed. The results show that the upper No. 5 coal seam in Baizi Coal Mine can be mined safely. Compared to the traditional method, which simplifies all the upper loads to uniform loads, the new method is safer. The system stability of the suspended roof and coal pillar is influenced by " a / L " and " L. " Axial stress curves of the coal pillar and suspended roof appear nearly parabolic with " a / L " varying. Their maximum values are obtained when the " a / L " value is around 0.5∼0.6. In this situation, the combination structure is most easy to to be damaged. The ratio q ′ / q has a linear relationship with all stresses of the system model. The failure sequence of the system model is determined by analyzing the relationship between the tensile strength of the suspended roof and compressive strength of the coal pillar. This study provides a reference case for coal resources upward mining under similar conditions.